2015
DOI: 10.1063/1.4937782
|View full text |Cite
|
Sign up to set email alerts
|

Oblique solitary waves in a five component plasma

Abstract: Multi-ion plasma is found in many regions of space like the earth's ionosphere, mesosphere, solar atmosphere, commentary environments, etc. Of this commentary plasma is of particular interest among researchers due to the presence of a wide variety of many species of ions: besides electrons and protons of solar origin, photoionization causes the production of H + and O + from water molecules present in the commentary atmosphere in addition to the associated photo-electrons [1]. Also, several positively charged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…note that the analysis done by Gombosi et al (2015) assumed singly charged nanograins; however, other analyses, for example, by Sijo et al (2015), include multiply charged grains.…”
Section: 1029/2019gl086147mentioning
confidence: 99%
“…note that the analysis done by Gombosi et al (2015) assumed singly charged nanograins; however, other analyses, for example, by Sijo et al (2015), include multiply charged grains.…”
Section: 1029/2019gl086147mentioning
confidence: 99%
“…(2) we have also neglected all collisional terms that may arise due to the collisions between plasma and dust particles or vise-versa. These assumptions are valid as long as the collision frequency or the ionization/ recombination rates are much less than the frequency of the dust ion acoustic waves under the consideration, and these have been investigated by many authors [1,18,19,20,21,22,23,24,25,26,27,28,29,30] to study linear [1] and nonlinear [18,19,21,21,22,23,24,25,27,28,29,30] dust ion acoustic waves.…”
Section: Model Equationsmentioning
confidence: 99%
“…However, if dissipation is very small, the shock wave will have an oscillatory profile of which the first few oscillations at the wavefront will be close to solitons [9,18,30]. Many authors showed that there are many space plasma and laboratory dusty plasma situations [8,11,19,24,31,32] in which the effects causing the dissipation can be insignificant compared to that of the dispersion [8] that lead to the formation of dust ion acoustic solitary wave structures.…”
Section: Model Equationsmentioning
confidence: 99%
See 2 more Smart Citations